“Estudio del comportamiento agronómico de tres variedades de Perejil (Petroselinum crispum), sembradas mediante sistema hidropónico con sustrato sólido, en la zona de Babahoyo - Ramírez Segura, Danilo (2011)
The present investigation work was carried out in the urban parish The Jump, with the Association FREMUBA (Front of Women of Babahoyo) in the properties of the complex Educational Unit "MARÍA ANDREA", located in the kilometer 2 ½ of the road Barreiro-Babahoyo. It was used as material genetic certified seed of the varieties of Parsley: “Dark Green”, “Moss Curled” and “Green River.” The treatments were the three varieties of parsley and the subtratamientos they were five dose of nutritious solution. 3 repetitions were had and the design experimental compound number was used “you Parcel Divided.” During the development of the rehearsal they were carried out all the works and practical agricultural that requires the cultivation for their normal vegetative and physiologic development of the plant like elaboration of the nursery; preparation of the basis; it transplants; siembra; I water, control of overgrowths; fertilization; control of plagues and illnesses; it harvests. The following parameters were also evaluated: root longitude, plant height, leaf longitude, plant weight, volume radical biomass, yield of the cultivation and economic analysis.